Analisis hubungan kekeluargaan dalam perilaku politik masyarakat pada pemilihan Kepala Desa Aro tahun 2022 - Amanda, Hanifa Triyuli; Anderson, Irzal; Kuswanto, Kuswanto (Academy of Education Journal, 2024)
This research aims to determine family relationships in community political behavior during the 2022 Aro Village Election. A descriptive qualitative approach was used in this research. It can be concluded that the sociological approach is influential in this research, namely that family relationships have a strong relationship in politics. Researchers found in the field that the people of Aro Village made their political choices during the village elections based solely on family relationships. The level of kinship/kinship in Aro Village is based on three (3) levels, namely the first kinship level, the second kinship level, and the third kinship level. Of the three levels of kinship, the one that has the most influence on vote acquisition is the second type of kinship, namely kinship/kinship based on the descent of the paternal and maternal grandmothers. The family of candidate one will be used as the winning team for the 2022 Aro Village Election. Likewise with candidate two. When compared with candidate two, the family of candidate one has a strong influence on vote acquisition. So that candidate one succeeded in winning the 2022 Aro Village Election. The public considers when choosing based on Subjective Emotional, namely making a choice because they have family ties, kinship, even friendship.